Perancangan Perangkat Keras MPPT Metode Perturb and Observation - Safarudin, Yanuar Mahfudz; Mariani, Dina; Hendrawati, Dwiana; Suwarti, Suwarti; Ali, Machrus; Nurrohmah, Hidayatul (Jurnal Sustainable: Jurnal Hasil Penelitian dan Industri Terapan, 2018)
This study discusses the use of perturb and observation algorithm in the application of maximum power point tracking. The algorithm is simulated and tested hardware in two shading conditions. The results show the similarity result of hardware testing and simulation.